3D‐Bioassembly of VH‐Spheroids for Cartilage Regeneration: in Vitro Evaluation of Chondrogenesis, Fusion and Lateral Integration. Issue 31 (25th September 2022) - Veenendaal, Laura; Longoni, Alessia; Hooper, Gary J.; Lim, Khoon S.; Woodfield, Tim B. F.; Lindberg, Gabriella C. J.
Abstract: Lateral integration and fusion of cartilage tissue interfaces remain significantly challenging and limits success of cartilage tissue engineering (TE) strategies. In this study, self‐assembled vitreous humor (VH) spheroids are fabricated by seeding clinically relevant human articular chondrocytes (hACs) or human mesenchymal stromal cells (hMSCs) in four VH hydrogels with different glycosaminoglycans (GAG) and protein content. Quantitative and qualitative analysis of the VH spheroids revealed that hAC‐VH spheroids are dependent on the initial GAG content of VH hydrogels to achieve successful chondrogenesis. Remarkably, uniform GAG and collagen type II distribution is found in all hMSC‐VH spheroids, independent of the VH donor. HMSC‐VH spheroids are therefore further evaluated for downstream applications by tracking cellular migration, and evaluating neotissue formation at the tissue‐tissue interface of cartilage spheroids 3D‐bioassembled into an in vitro fusion model to asses fusion and integration. hMSC‐VH spheroids enhanced multidirectional cellular migration of both hACs and hMSCs toward the tissue‐tissue interface, and consequently supported dense GAG and collagen type II deposition at the integration region. Ultimately, hMSC‐seeded VH spheroids display successful chondrogenesis and endorse fusion and integration of cartilage tissue interfaces through upregulated cellular migration of clinically relevant cell sources – key elements for clinical translation of cell‐based TE strategies. Abstract : Successful chondrogenic differentiation of human articular chondrocytes (hACs) is only observed when encapsulated in glycosaminoglycan (GAG)‐rich vitreous humor (VH) hydrogels. Healthy tissue formation is however achieved in all human mesenchymal stromal cells (hMSC)‐VH spheroids, independent of the VH composition. HMSCs‐VH spheroids fulfil clinically relevant requirements for cartilage building blocks for bottom‐up tissue engineering (TE): reproducible chondrogenesis, fusion and integration.